Ekspresi BMP2 dan TRAF6 pada Jaringan Periodontal setelah Pemberian Ekstrak Kopi Robusta selama Pergerakan Gigi Ortodonti - Herniyati Herniyati; Leliana Sabdra deviade Putri; Hestieyonini Hadnyanawati; Happy Harmono (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
Orthodontic tooth movement occurs due to mechanical stimulation followed by alveolar bone and periodontal ligament remodeling. Bone remodeling is the process of bone resorption in areas of tension and bone formation in areas of tension. Various techniques and drugs are used to speed up orthodontic treatment. This study aims to analyze the expression of BMP2 and TRAP6 on orthodontic tooth movement after the administration of Robusta coffee extract. Twenty-four Wistar rats were divided into 4 groups: C1 (2 weeks) and C2 (3 weeks) groups: rats were given orthodontic mechanical force (OMF) and T1 (2 weeks) and T2 (3 weeks) groups rats were given OMF and Robusta coffee extract. OMF in rats was performed by moving the maxillary right permanent molars mesially with a Niti closed coil spring. Observations were made on the 15th and 22nd day by immunohistochemical examination to determine the expression of BMP2 and TRAP6. Administration of Robusta coffee extract for 2 weeks and 3 weeks increased BMP2 and TRAP6 expression (p <0.05). Administration of Robusta coffee extract increased the expression of BMP2 and TRAP6 in the alveolar bone during orthodontic tooth movement.